Escherichia coli multilocus sequence type 38 from humans and broiler production represent distinct monophyletic groups - Mo, Solveig Sølverød; Fiskebeck, Eve Zeyl; Slettemeås, Jannice Schau; Lagesen, Karin; Nilsson, Oskar; Naseer, Umaer; Jørgensen, Silje Bakken; Thorsteinsdottir, Thorunn Rafnar; Sunde, Marianne (Frontiers in Microbiology, 2023)
Escherichia coli belonging to multilocus sequence type 38 (ST38) is a well-known cause of extra-intestinal infections in humans, and are frequently associated with resistance to extended-spectrum cephalosporins (ESCs). Resistance to carbapenems, mediated by blaOXA-genes has also been reported in this ST. Recently, the European Centre for Disease Prevention and Control (ECDC) released a rapid risk assessment on the increased detection of OXA-244 producing E. coli ST38 in humans, requesting further knowledge to determine the source. ST38 is also one of the most common STs among ESC-resistant E. coli from broiler production. Our aim was to investigate the genetic characteristics and relationship between E. coli ST38 from broiler production and humans, and to investigate if there has been a potential spillover between these sources. A total of 288 E. coli ST38 genomes isolated from humans in Europe (collected 2009-2019) and from Nordic broiler production (collected 2011-2014) were analyzed. The results showed distinct monophyletic clades associated to humans and broiler production. Furthermore, there were differences in the ESC resistance genes present in E. coli ST38 from the two sources. The blaOXA-244 gene was not present in E. coli from broiler production. Our results show that ST38 from humans and broiler production belong to well-separated clades, and suggest that the increased detection of OXA-244-producing E. coli ST38 in humans is not associated with spillover from broiler production.